Ganglion cell layer thickening in well‐controlled patients with type 1 diabetes: an early sign for diabetic retinopathy?. Issue 3 (25th October 2019) - Gerendas, Bianca S.; Hatz, Katja; Kaider, Alexandra; Zulewski, Henryk; Lehmann, Roger; Montuoro, Alessio; Schmidt‐Erfurth, Ursula; Pruente, Christian
Abstract: Purpose: To evaluate early changes in retinal layers using optical coherence tomography (OCT) in patients with long‐standing type 1 diabetes (DM1) receiving intensified insulin therapy. Methods: In a cross‐sectional case–control study 150 patients with DM1 and 150 age‐ and sex‐matched healthy control participants underwent OCT imaging. Scans of both eyes were analysed for different layers (NFL, GCL (+IPL), INL, outer layer complex (OLC, including OPL, ONL and ELM) and photoreceptors (PR)) in all subfields of an ETDRS grid. All analyses were performed semi‐automatically using custom software by certified graders of the Vienna Reading Center. ANOVA models were used to compare the mean thickness of the layers between patients and controls. Results: Six hundred eyes with 512 datapoints in 49 b‐scans in each OCT were analysed. Mean thickness in patients/controls was 31.35 μ m/30.65 μ m (NFL, p = 0.0347), 76.7 μ m/73.15 μ m (GCL, p ≤ 0.0001), 36.29 μ m/37.13 μ m (INL, p = 0.0116), 114.34 μ m/112.02 μ m (OLC, p < 0.0001) and 44.71 μ m/44.69 μ m (PR, p = 0.9401). When evaluating the ETDRS subfields separately for clinically meaningful hypotheses, a significant swelling of the GCL in patients could be found uniformly and a central swelling for the OLC, whereas the distribution of NFL and INL thickening suggests that their statistical significance was not clinically relevant. Conclusion: These preliminary results demonstrate that preclinical retinal changes in patients with long‐standing DM1 can be found by retinal layer evaluation. However, the changes are layer‐specific, with significant thickening of the GCL and less so of the OLC suggesting a role as an early sign for diffuse swelling and the evolution of DME even in well‐controlled diabetes.